PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP TINGKAT KEMANDIRIAN KEUANGAN PEMERINTAH DAERAH PROVINSI SUMATERA BARAT - Siti Nurvaliza; Gerry Hamdani Putra (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to re-examine previous research between independent variables, namely regional original income and general allocation funds on financial independence. The object of this research is Financial Independence and the subject of this research is the Regional Government of West Sumatra Province 2020-2022. The population in this research is the report on the realization of the revenue budget, regional expenditure and regional income of the Regional Government of West Sumatra Province. The type of data in this research uses a quantitative approach. The data source used is secondary data, namely data collected from existing records. The sample used in this research is the realization report of the APBD (Regional Income and Expenditure Budget) of the Regency/City Government of West Sumatra Province which has been audited by BPS with a total of 19 samples. The results of this research indicate that Regional Original Income has a positive effect on regional financial independence. Meanwhile, the General Allocation Fund has a negative effect on regional financial independence